Implementation of Switching Algorithm for SVPWM Inverter in Induction Motor Drive System on Electric Vehicle Applications - Bayu Praharsena; Mohammad Jauhari; Era Purwanto; Mentari Putri Jati; Angga Wahyu Aditya; Aries Alfian Prasetyo (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
Electric cars are the way to reduce global warming and fuel shortages. Performance variable speed drive is needed for various drive electric vehicle applications. Unfortunately, high performance is still being investigated with a variety of drive systems. This paper presents a design, analysis, and implementation of the SV-PWM inverter motor drive system. The SV-PWM algorithm in design using Matlab, to analyze the system include signal response, THD-V, THD-I. All algorithms are embedded in STM32F4, as the main controller. The hardware uses a 3-phase motor control Steval power module. Response speed and output signal inverters are shown in chart form for analysis